Sources of uncertainty in estimation of climate velocity and their implications for ecological and conservation applications - Carlos Carroll; Colin R. Mahony (Conservation Science and Practice)
Abstract The velocity of climate change, which estimates the migration speed necessary to maintain constant climatic conditions, is increasingly used to map climate‐related threats to biodiversity. Using newly developed climate velocity data for North America to 2100 based on an ensemble of current‐generation climate projections, we asked how important differing sources of uncertainty from global climate model projections are, how the magnitude of this uncertainty compares with the internal variability of the climate system, and what aspects of climate velocity are robust to such uncertainty. We found that most variation was due to contrasts among global climate models, followed by variation among alternative emissions pathways. However, correlation was great enough (0.817) to allow application of velocity to inform conservation and management. In contrast, internal variability (i.e., weather at multidecadal timescales) resulted in low correlation between simulated and observed velocity for the 2001–2020 period. A null model using current baseline climate data and assumed uniform 2° heating was moderately correlated with velocity from ensemble future projections, helping to identify model‐independent velocity patterns difficult to capture via rules such as protection of elevational gradients. Such uncertainty analyses are essential for informed application of velocity and other climate exposure metrics.